TEACHING SEXUALLY TRANSMITTED INFECTIONS TO UNDERGRADUATE NURSING STUDENTS IN BRAZIL - Petry, Stéfany; Padilha, Maria Itayra (Cogitare Enfermagem, 2024)
Objective: To identify the approach to Sexually Transmitted Infections within Undergraduate Nursing Courses at Federal Universities in Brazil from 1972 to 2023. Method: Qualitative, historical, and social study, using oral and documentary sources. Interviews were conducted with 23 professors from five undergraduate nursing courses in Brazil. For data analysis, the software Atlas.ti version 9.0 and also Content Analysis were used. Results: Three categories were listed: "Strategies and actions carried out in the teaching of Sexually Transmitted Infections", "Articulation of teaching with public policies" and "Acting as a teacher on the subject". Conclusion: Teaching involves health education, nursing consultation, diagnosis, and treatment in practical and theoretical classes, emphasizing women’s and adult health subjects. Teachers have autonomy in how teaching is offered to students in terms of content, strategies, and the use of public policies.